European integration and the prospects for the Baltic states - Vareikis, Egidijus (Politologija, 1997)
This article debates a large number of problems. One of the essential problems is the chances of the Baltic States in the process of the European Integration. Viewing purposes of entering EU and NATO as the main destinations of the Baltic States’ foreign policy, the author propounds a conceptual review on this problem (so far as it does not restrict itself within the wish and the attitude of the three Baltic States, but reaches far beyond it and inevitably postulates universal complexity of this problem). Consequently, the author proceeds to the elucidation of the issues due to which the identification of the geopolitical status of the Baltic States becomes problematic. Thus, in the first part of the article, validity of the obsolete classifications of the states according to which states were forced to fall under one of the two categories (that is, West or East) is challenged. The author questions that in contraposition to the tolerant Act of the Conference on Security and Cooperation in Europe, end 1990, and claims that the establishment of the new classification is necessary. Speaking about the Baltic States, the author claims that in the process of integration, the Baltic States must not be indifferent to which geopolitical sphere they are attached. We face the refusal of the acceptability of several worldwide spread geopolitical divisions which belay different identifications on the Baltic States: the first one is a Russia-propagated approach which assigns three Baltic countries to the "former USSR" territory, it constantly intensifies and becomes more important (the author claims that this standing is enormously dangerous and has already forced the Baltic States to the condition of a victim); the second one states that identification of "a bridge" between West and East is detrimental, and the third point argues that the exposure of the Baltic States in the place of "Europe’s Centre" is futile as well. The author illustrates these propositions with a wide range of arguments. It is discerned that a newly proposed CEC-10 category is the most suitable and compromising deal. Contemporary acute aspects of the Baltic de-unification are posed to be discussed. The author proceeds and not only states the exclusiveness of the Baltic States but also postulates an argument of a distinct perspective that EU expansion would expose. Four positive reasons why EU would tend (not avoid) to expand, of which consolidation of the continental security appears to be the most challenging, are displayed. Nevertheless, the second part of the article researches economic and political aspects of EU expansion and debates not only those positive sequels but also presents a list of the difficulties (six) that shall be faced and tackled soon. The author claims and discusses the problem that the status of the Baltic States in building a European security system still is not established. Vareikis analyzes means and enrollment due to which the Baltic States seek and approach the entry into the mentioned organizations. Obstacles to barrier these desires are additionally enumerated. This article thrusts the reader on a detailed consideration of the problem.